(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2018)
This study aims at revealing the mechanisms of religious intertextuality used by Al-Jahez in his book “The Messages”, especially the Message of Nostalgia. The student discusses definitions that are linguistically similar. That is: structural level, textual linguistics, textual criteria, and intertextuality in general and religious intertextuality in particular. In addition, it aims at presenting the most prominent roles of textual linguistics, intertextuality, religious intertextuality, together with finding the linguistic evidences for the structures of the religious intertextuality in the message of Al-Jahez” Nostalgia” with full explanation and analysis to this message depending on the methodology of structural level which includes the sciences of both syntax and morphology.